The Effect of Loan Interest Rates and Inflation Rates on Net Profit Growth at Commercial Banks Listed on the IDX - Abdul Hamid; Syahrial Hasanuddin Pohan; Adera Feby Mutia; Alboi Jayanta Naibaho; Rani Ramadhani Nasution (Proceeding of The International Conference on Economics and Business, 2022)
This research was conducted to determine the influence of interest rates and inflation on the net profit growth of publicly listed commercial banks in the Indonesia Stock Exchange. Data was collected from www.idx.co.id, spanning from 2017 to 2021. The study took place from March to August 2022. The population for this research comprised 43 companies, with a sample size of 20 companies. The research employed quantitative data processed using Eviews 9 with the panel data regression method. The test results concluded that the interest rate variable, partially, does not have a significant impact on the net profit growth. However, inflation, partially, has a significant effect on the net profit growth of commercial banks during the period from 2017 to 2021. Simultaneously, interest rates and inflation do not have a significant impact on the net profit growth of commercial banks. The contribution of the interest rate and inflation variables to net profit growth is only 5.66%, and the correlation between the interest rate and inflation variables with net profit growth is weak.